Perlindungan Hukum Terhadap Konsumen Pada Sepeda Motor Dengan Rangka Esaf Yang Patah - Saputra, Rizki Agung; Warka, Made (Journal Evidence Of Law, 2024)
This study aims to analyze the legal protection of motorcycle consumers with broken eSAF frames. This type of research uses a prescriptive normative juridical method with the Statue Approach and Conceptual Approach methods. Using primary and secondary legal materials by inventorying and conducting literature studies. The results of this study indicate that consumers who feel harmed by goods that should not be distributed by business actors as producers, causing losses or accidents, will get protection related to their rights as consumers in accordance with Article 1504 - Article 1512 of the Criminal Code. Producers as business actors if they violate prohibitions in carrying out their obligations so as to cause damage / loss, it is mandatory for business actors to pay compensation in the form of compensation for money, goods and / or services. However, in Article 27 of the GCPL, producers or business actors are exempted from paying compensation or replacing goods and / or services if it is proven that the goods are not intended for distribution, defects in the goods arise at a later date, if the defect is caused by consumer non-compliance with the feasibility, consumer negligence and the agreed agreement ends.